Effective Community Response to Disaster: Exploring the Role of Community Emergency Response Teams - Mark A. Brennan (EDIS)
FCS9255, a 3-page fact sheet by M.A. Brennan, is part of a series of discussions on the impact of community action in response to natural and other disasters. This paper describes a relatively new approach to local involvement in disaster response that is emerging across counties and communities in the United States, the Community Emergency Response Team (CERT) program. Includes references, suggested reading, and links to useful Web sites. Published by the UF Department of Family Youth and Community Sciences, July 2006.